2021
DOI: 10.3390/rs13142796
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Northern Hardwood Forest Inventory Attributes Using UAV Laser Scanning (ULS): Transferability of Laser Scanning Methods and Comparison of Automated Approaches at the Tree- and Stand-Level

Abstract: UAV laser scanning (ULS) has the potential to support forest operations since it provides high-density data with flexible operational conditions. This study examined the use of ULS systems to estimate several tree attributes from an uneven-aged northern hardwood stand. We investigated: (1) the transferability of raster-based and bottom-up point cloud-based individual tree detection (ITD) algorithms to ULS data; and (2) automated approaches to the retrieval of tree-level (i.e., height, crown diameter (CD), DBH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…The sensitivity analysis with increasing raster cell sizes as a proxy for decreasing point density suggests that our best models could perform similarly using ALS data instead of TLS, providing point density is greater than 16 pts/m 2 . While the point density of ALS and DLS (laser scanning from drones) point clouds is dependent on the flight altitude and speed, number of flight lines, and scan and pulse rates, the 16 pts/m 2 threshold is attainable by both ALS and DLS [85][86][87]. This threshold is also consistent with the one suggested in a recent study for height estimation of coniferous trees using drone-based LiDAR point clouds of different point densities, which found that height accuracy only worsens at below 17 pts/m 2 [73].…”
Section: Crown Area Sensitivity Analysismentioning
confidence: 99%
“…The sensitivity analysis with increasing raster cell sizes as a proxy for decreasing point density suggests that our best models could perform similarly using ALS data instead of TLS, providing point density is greater than 16 pts/m 2 . While the point density of ALS and DLS (laser scanning from drones) point clouds is dependent on the flight altitude and speed, number of flight lines, and scan and pulse rates, the 16 pts/m 2 threshold is attainable by both ALS and DLS [85][86][87]. This threshold is also consistent with the one suggested in a recent study for height estimation of coniferous trees using drone-based LiDAR point clouds of different point densities, which found that height accuracy only worsens at below 17 pts/m 2 [73].…”
Section: Crown Area Sensitivity Analysismentioning
confidence: 99%
“…Meanwhile, previous research has found variable accuracies when using ALS to estimate other attributes of individual trees. Several studies have found RMSEs for DBH estimates in the range of 4-8 cm [14,18,[36][37][38]. Using high-density ALS point clouds, Hyyppä et al [9] improved the accuracy to 2-3 cm (6-10%) by automatically detecting stem arcs, i.e., horizontal clusters of laser hits to the tree stem obtained during a brief period of time.…”
Section: Related Workmentioning
confidence: 99%
“…On the one hand, several methods have been based on infrastructure, which derives the location from distance information to anchors, such as GPS [9], motion capture system (MCS) [10], ultra-wideband (UWB) [11], etc. On the other hand, some on-board sensors (e.g., electro-optical devices [12], vision sensors [13,14] and laser scanners [15]) have been used to calculate the distance between the UAV and docking target in order to locate the target. The common knowledge is that GPS is cheap and relatively mature.…”
Section: Introductionmentioning
confidence: 99%